2004
DOI: 10.1074/jbc.m404109200
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-induced Quisqualic Acid and Ibotenic Acid Affinity at the Metabotropic Glutamate Receptor Subtype 4

Abstract: The metabotropic glutamate receptors (mGluRs) are key modulators of excitatory neurotransmission in the central nervous system. The eight mGluR subtypes are seven trans-membrane-spanning proteins that possess a large extracellular amino-terminal domain in which the endogenous ligand binding pocket resides. In this study, we have identified four non-conserved amino acid residues that are essential for differentiating mGluR1 from mGluR4. Our approach has been to increase the affinity of the classic mGluR1 agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…3). A role for this residue in ligand recognition is consistent with previous reports that the mGluR7 mutant N74K decreased the EC 50 of the group III-specific synthetic agonist L-AP4 by about 10-fold as compared with wild type mGluR7 (41), and that a K74Y mutation in mGluR4 enhanced its affinity for the mGluR1-specific synthetic agonist ibotenic acid (42). However, the evolutionary and functional significance of this residue can only be understood in the context of the endogenous ligands with which the receptors have been challenged over the course of evolution.…”
Section: Discussionsupporting
confidence: 78%
“…3). A role for this residue in ligand recognition is consistent with previous reports that the mGluR7 mutant N74K decreased the EC 50 of the group III-specific synthetic agonist L-AP4 by about 10-fold as compared with wild type mGluR7 (41), and that a K74Y mutation in mGluR4 enhanced its affinity for the mGluR1-specific synthetic agonist ibotenic acid (42). However, the evolutionary and functional significance of this residue can only be understood in the context of the endogenous ligands with which the receptors have been challenged over the course of evolution.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, amino acid residues that are responsible for the pharmacological selectivity of group I relative to group III metabotropic have been identified [15]. Mutation of a few non-conserved amino acids in the mGluR4 receptor to those in mGluR1 conferred the ability to bind the group I selective agonists quisqualate and ibotenic acid on the mGluR4 receptor [15]. These residues in mGluR4 were in both lobe 1; Lys74, and lobe 2; Glu287, Ser313 and Lys317.…”
Section: Ligand Binding Domain Structure and Functionmentioning
confidence: 98%
“…Several of the key residues for agonist binding in mGluR4, Arg78, Ser159, Thr182, and Lys405, are highly conserved residues in all of the mGluRs and are implicated in agonist binding in the mGluR1 LBD structure [6]. Recently, amino acid residues that are responsible for the pharmacological selectivity of group I relative to group III metabotropic have been identified [15]. Mutation of a few non-conserved amino acids in the mGluR4 receptor to those in mGluR1 conferred the ability to bind the group I selective agonists quisqualate and ibotenic acid on the mGluR4 receptor [15].…”
Section: Ligand Binding Domain Structure and Functionmentioning
confidence: 99%
“…In another modeling study on the same subgroup of mGluRs, it was shown that the pharmacological profile of the Group III receptor, mGluR4, could be completely switched via mutagenesis to a receptor that responded to the Group I specific agonists quisqualic acid and ibotenic acid [78]. Based on the homology model, residues K74, E287, S313 and K317 in mGluR4 were mutated to the corresponding residues in mGluR1.…”
Section: The Ligand Binding Domain Of Family C Gpcrsmentioning
confidence: 99%